Exploring the Impact and Acceptance of Wearable Sensor Technology for Pre- and Postoperative Rehabilitation in Knee Replacement Patients: A U.K.-Based Pilot Study. Issue 2 (27th April 2022) - Cooper, D.M.; Bhuskute, N.; Walsh, G.
Abstract : Background: Knee replacement operations are common, highly successful procedures that are increasing in frequency. The COVID-19 pandemic has emphasized the need for innovative care pathways that reduce face-to-face appointments. We report on the impact of introducing a wearable sensor for pre- and postoperative rehabilitation of 21 knee replacement patients at 2 hospitals in the U.K. Methods: The sensor (BPMpathway; 270 Vision) was provided during joint school prior to knee replacement and stayed with the patient until a maximum of 9 weeks post-surgery. Participant progress and exercise were monitored remotely, with exercise regimens altered as required. Participants and clinicians could communicate remotely via the device. Results: The median range of motion during the first week post-surgery was 63° (interquartile range [IQR] = 21°) and increased to 136° (IQR = 16°) by week 7. The rate of participant compliance with exercises using the device was 32.3% for thrice-daily compliance and 52.4% for once-daily compliance. The 2-way communication channel was well utilized by both participants and clinicians. We report a 35.7% reduction in face-to-face physiotherapy appointments compared with standard practice. Finally, >80% of users who completed the feedback questionnaire reported a positive experience using the device, finding it easy to understand and reporting that it motivated them to perform their exercises. Conclusions: The use of BPMpathway was well received, effective, and reduced face-to-face physiotherapy appointments. Clinical Relevance: Remote monitoring can reduce the burden to the outpatient physiotherapy service by supporting the post-COVID-19 surgical service recovery plans of the National Health Service and allowing patients to recuperate at home.